2021
DOI: 10.3389/fneur.2021.779712
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Olfactory Dysfunction With Depression, Cognition, and Disease Severity in Parkinson's Disease

Abstract: Background: Non-motor subtypes of Parkinson's disease (PD) include the limbic, cognitive, and brainstem phenotype, which may have different pathological pathways with olfaction. In this work, we aim to clarify the association between olfactory dysfunction, depression, cognition, and disease severity in PD.Methods: A total of 105 PD subjects were included and divided into anosmia and non-anosmic groups, using the University of Pennsylvania Smell Identification Test (UPSIT). All patients were evaluated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…The PDQ-39 COG dimension has been shown to correlate with individual neuropsychological tests [ 38 ], individual cognitive domains [ 39 ], and depression [ 39 ]. Our previous studies suggested there is a close relationship between dysosmia and impaired cognition according to neuropsychological testing [ 13 , 14 ], but there seemed to be a lack of correlation between dysosmia and depression [ 13 , 40 ]. The findings in our study revealed similar results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PDQ-39 COG dimension has been shown to correlate with individual neuropsychological tests [ 38 ], individual cognitive domains [ 39 ], and depression [ 39 ]. Our previous studies suggested there is a close relationship between dysosmia and impaired cognition according to neuropsychological testing [ 13 , 14 ], but there seemed to be a lack of correlation between dysosmia and depression [ 13 , 40 ]. The findings in our study revealed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…These non-motor symptoms include cognition, psychiatric, sleep, autonomic disturbance, and pain symptoms. Although anxiety, apathy, sleep, and autonomic disturbance have been correlated with dysomia [ 3 , 4 , 44 ], depression is still a matter of debate [ 3 , 4 , 13 , 40 ]. Furthermore, there is no pathophysiological basis for the relationship between pain and dysosmia at present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies evaluated the correlation between olfactory deficit and cognitive impairment in PD [8][9][10][11][12][13] demonstrating that olfactory dysfunction may increase the risk of dementia up to ten years after PD diagnosis regardless of baseline cognitive function [14], the involved specific cognitive domains are largely undetermined. To date, only a single study explored whether Mild Cognitive Impairment (MCI) and the involvement of each single cognitive domain may influence olfactory function in PD patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…The olfactory bulbs project to brain regions that play a vital role in emotion and cognition, such as the orbitofrontal cortex, hippocampus, and amygdala ( Kohli et al, 2016 ). A large amount of evidence shows that OD is related to various neuropsychiatric disorders, including depression and anxiety ( Fang et al, 2021 ). Functional and structural damage to the olfactory system, particularly the olfactory bulbs and olfactory epithelium, are common in patients suffering from depression ( Zuo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%